Black skin, black mask: the subaltern's quest for transformation in Jean-Paul Civeyrac's Mon amie Victoria. Issue 1 (2nd January 2020) - Oancea, Ana
ABSTRACT: In Mon Amie Victoria/ My Friend Victoria (2014) Jean-Paul Civeyrac's representation of the marginalisation of his protagonist, a young black woman in contemporary Paris, problematises both race difference and socio-economic status. Starting from her low affect display, this article identifies two opposing theoretical masks through which it analyses her motivation. The author initially reads Victoria in a Fanonian manner, alienated and powerless to create the meaning of her 'white mask'. However, a black Noh mask, with which she appears to identify, advises the informed viewer that real transformation is possible. Japanese tradition imagines that such masks allow actors to become, not merely play, diverse characters. A great difference in agency thus exists between the masks, though both answer Victoria's need to be recognised. Civeyrac's reluctance clearly to illustrate the protagonist's two avatars requires us to draw on his experimental films as well as intertexts with two other similarly themed films, Ousmane Sembène's La Noire de. . ./Black Girl (1966) and Sang- soo Im's Hanyo/The Housemaid (2010). In reading Victoria through their subaltern protagonists, the author elucidates the parameters in which her active and passive avatars operate, concluding that the opportunity for change is more limited than the Noh mask promises.